Postmortem submersion intervals in the River Thames - Greatbatch, Ian; Livingstone, David; Hunter, Gordon; Saunderson, Yvonne (Journal of search & rescue, 2023)
This paper catalogues a dataset drawn from Metropolitan Police records in the period 2004-2015 regarding drowning victims recovered from a tidal stretch of the River Thames and provides a comparative study with a similar dataset from the time period 1956-1959 by the County of London (Western District), H.M. Coroner of that time, Gavin Thurston, from the information gathered in his professional role. In addition to drawing comparisons between these time periods the paper draws inferences regarding the Post-Mortem Submersion Interval (PMSI) and proposing further study required. Both datasets show a significant bias towards male subjects counter to other comparable data in the literature. This bias is even more pronounced in the 2004-2015 period where additionally there are significantly more incidents during Full Moon Lunar Phase. Some weak seasonal trends were observed regarding equinoctial peaks but these were not statistically significant. There are few clear trends observable in factors that might influence Post-Mortem Submersion Interval although there was a weak and counter-intuitive inverse relationship between clothing weight and time in water. KEY WORDS: PMSI, Drowning, GIS